Perspektif Hak Asasi Manusia dalam Perlindungan Hak Kekayaan Intelektual Atas Pengetahuan Tradisional dan Ekspresi Budaya Tradisional Masyarakat Adat - Rahjanto Rahjanto (Jurnal HAM, 2014)
These days a lot of intellectual properties in the form of traditional knowledge and traditional cultural expressions, which are created or originated from indigenous peoples, have become popular around the world, for example: works of art and medicine, and internationally traded that worth up to multibillion dollar U.S. each year. Most of the revenue from the trade is eventually in the hands of companies outside the area of origin of the intellectual property, and more often in the hands of foreign companies. This research uses a qualitative approach, while the data collection conducted at eight locations: West Java, Yogyakarta , Central Sulawesi, South Kalimantan, Bali, North Sumatra, South Sumatra , East Nusa Tenggara. In terms of legality, the state has not provided adequate legislations to protect intellectual property such as traditional knowledge and traditional cultural expressions. Arguably, Article 10 paragraph (2) of the Law No. 19/2002 on Copyright is not entirely appropriate (or compatible) with the characteristics of traditional knowledge and traditional cultural expressions. Hence, the Indonesian government ought to take progressive steps by regulating traditional knowledge and traditional cultural expressions into a separate law (sui generis).